Sequential therapy for pancreatic cancer by losartan- and gemcitabine-loaded magnetic mesoporous spheres. Issue 34 (25th June 2019) - Li, Yanjun; Tang, Yuxia; Chen, Sui; Liu, Ying; Wang, Shouju; Tian, Ying; Wang, Chunyan; Teng, Zhaogang; Lu, Guangming
Abstract : Sequential therapy has attracted increasing attention for cancer treatment, in which multiple drugs can be used to enhance the therapeutic efficacy. Abstract : Sequential therapy has attracted increasing attention for cancer treatment, in which multiple drugs can be used to enhance the therapeutic efficacy. In this work, sequential therapy is demonstrated using amino functionalized Fe3 O4 embedded periodic mesoporous organosilica spheres (Fe3 O4 @PMO-NH2 ) and Fe3 O4 @PMO as drug carriers. Losartan can inhibit type I collagen and hyaluronic acid of the pancreatic cancer matrix, which is safe and inexpensive, and does not increase the risk of tumor metastasis. First, losartan is loaded in the Fe3 O4 @PMO-NH2 (Fe3 O4 @PMO-NH2 -Los) to treat pancreatic cancer. Immunohistochemistry staining of tumor slices after treatment with Fe3 O4 @PMO-NH2 -Los confirms that collagen and hyaluronan acid are significantly reduced. The major solid components in the extracellular matrix of the tumor are reduced, which facilitates the penetration of nanodrugs into the tumor site. Afterward, gemcitabine loaded Fe3 O4 @PMO (Fe3 O4 @PMO-Gem) is sequentially delivered to treat pancreatic cancer, which shows strong killing ability for the pancreatic cancer cells. Comparing with a saline group, the tumor volume treated with Fe3 O4 @PMO-NH2 -Los, Fe3 O4 @PMO-Gem, and Fe3 O4 @PMO-NH2 -Los + Fe3 O4 @PMO-Gem decreases to 92.6%, 60.7%, and 28.6%, respectively, suggesting that the sequential therapy significantly inhibits pancreatic tumor growth compared to the mono-therapy strategy. Taken together, this study provides a promising approach for nanomaterials-based sequential therapy for pancreatic cancer treatment.